2 Answers | Add Yours
There are multiple versions of this; the key is to try to find what is wrong with the "proof": Let a=b; then
`a^2=ab` Multiply both sides by a
`a^2+a^2=a^2+ab` Add `a^2` to both sides
`2a^2=a^2+ab` Collect like terms
`2a^2-2ab=a^2+ab-2ab` Subtract 2ab from both sides
`2a^2-2ab=a^2-ab` Collect like terms
`2(a^2-ab)=1(a^2-ab)` Distributive property
`2=1` Divide both sides by `a^2-ab`
Problem with the above solution is that you are dividing both sides with (a^2 - ab) which is zero because a=b (assumed).
Any quantity divided by zero is an indeterminate
You cannot divide by zero and that is what's wrong with the proof.
We’ve answered 317,944 questions. We can answer yours, too.Ask a question